2023
DOI: 10.3390/cancers15174367
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Chemotherapy Causes Growth Impairments, Vitamin D Deficiency, Bone Loss, and Altered Intestinal Metabolism—Effects of Calcitriol Supplementation

Yu-Wen Su,
Alice M. C. Lee,
Xukang Xu
et al.

Abstract: Vitamin D deficiency or insufficiency is prevalent in childhood cancer patients and survivors after chemotherapy; further studies are needed to investigate the underlying aetiology and effectiveness of vitamin D supplementation in preventing chemotherapy-induced bone loss. This study used a rat model of treatment with antimetabolite methotrexate to investigate whether methotrexate chemotherapy causes vitamin D deficiency and if vitamin D supplementation attenuates the resultant bone loss. Methotrexate treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…Moreover, they found that MTX chemotherapy affected the intestinal expression of enzymes crucial in vitamin D metabolism, resulting in an increased expression of CYP27B1 (responsible for converting 25-OH-D to active form) and then CYP24 (vitamin D catabolism). They also observed intestinal damage induced by MTX treatment, which can negatively influence vitamin D absorption from nutrients [14]. We observed a significantly decreased level of 25-OH-D in the summer group treated with MTX, compared with LEF-treated patients.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Moreover, they found that MTX chemotherapy affected the intestinal expression of enzymes crucial in vitamin D metabolism, resulting in an increased expression of CYP27B1 (responsible for converting 25-OH-D to active form) and then CYP24 (vitamin D catabolism). They also observed intestinal damage induced by MTX treatment, which can negatively influence vitamin D absorption from nutrients [14]. We observed a significantly decreased level of 25-OH-D in the summer group treated with MTX, compared with LEF-treated patients.…”
Section: Discussionmentioning
confidence: 51%
“…The authors considered such hypotheses as the deterioration of vitamin D3 bioavailability from nutrients, the downregulation of the hepatic hydroxylation of calciferol (due to the drug hepatotoxicity), and the disturbance of vitamin D3 skin synthesis [16]. A recent paper published by Su et al presents some interesting data concerning the effect of MTX chemotherapy on 25-OH-D levels in an animal model [14]. The authors confirmed that MTX treatment led to a significant decrease in 25-OH-D serum concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampicin administration to patients with idiopathic infantile hypercalcemia (IIH) due to loss-of-function mutations in CYP24A1 induces CYP3A4 , suggesting an alternative pathway for vitamin D inactivation [ 50 ]. In addition, methotrexate chemotherapy (which is commonly used in childhood oncology) leads to bone loss and decreasing serum 25OHD 3 along with altered intestinal Cyp24a1 [ 51 ]. During drug therapy in clinical practice, multiple drugs are frequently used, and adverse drug interactions can sometimes occur.…”
Section: Discussionmentioning
confidence: 99%